REALITI DAN PROSPEK INSTRUMEN PASARAN MODAL ISLAM DI MALAYSIA: KAJIAN KHUSUS TERHADAP BON ISLAM - Noordin, Kamaruzaman (Jurnal Syariah, 2019)
The existence of Islamic capital market since 1983 has contributed towards the development of Islamic-based economy in Malaysia. Since then, Islamic bond which is part of Islamic capital market instruments has been widely accepted and used by many companies to finance their mega projects. This article tries to explore the concepts and types of Islamic bond available as an alternative to conventional bonds. The peiformance of Islamic bonds as well as its prospects in Malaysia are also discussed in this paper.